Development of a brief assessment tool to identify children with probable anxiety disorders - Reardon, T; Ukoumunne, OC; Ball, S; Gray, A; Violato, M; iCATS Team; Creswell, C (Wiley, 2024)
Background Difficulties identifying anxiety disorders in primary-school aged children present significant barriers to timely access to support and intervention. This study aimed to develop a brief assessment tool that can identify children with anxiety disorders in community settings, with a high level of sensitivity and specificity.